Obraz luteranów w Rodzayu abo potomstwie […] piątego ewanyelisty i oyca (1561) - Klimek-Grądzka, Jolanta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
This article is a language-stylistic analysis of an anonymous translation of the Latin polemical text entitled The Kind, or the Descendants of Martin Luther, the Fifth Evangelist and the Father, who Gave Life to Evangelists and their Christian Congregations, who Fight against the Church of God and against Each Other. The analysis has determined that the main organizing principle of the text is the use of parallelisms and oppositions of the kind “sons of Christianity” v. “sons of Satan”, true (faith) v. sectarian (denomination), unity v. diversity. The evaluative narrative and the way in which the particular fractions within the Lutheran church are depicted illustrate a case of a well-balanced polemical, whose main objective is to prove the inferiority of the Reformed denominations.